Corporate Social Responsibility Practices in Selected Nepalese Companies - Shrestha, R. K.; Rai, B. (The Journal of Knowledge and Innovation, 2022)
Corporate Social Responsibility (CSR) is a business system through which the production and distribution of wealth are allocated for the betterment of its stakeholders. It includes the economic, legal, ethical, and philanthropic domains. It impacts society environmentally, socially, and economically. The paper aims to assess the practices of CSR in selected Nepalese companies and identify the disclosure of CSR activities. Nepal Telecom [NT], Ncell, Chaudhary Group [CG], and Standard Chartered Bank [SCB] are selected companies in this study. Data were collected through relevant documentary scrutiny and evidence such as annual reports and websites and review of previous research studies. The study is based on the qualitative method. Data analysis was used on a thematic basis. Convenience sampling was used. On the one hand, both NT and Ncell make their contribution on their communicating service; on the other hand, all of the sample companies focus their spending on education, health, environmental protection, natural calamities, and sports. Ncell has made a substantial contribution to protecting COVID-19. CG’s various CSR programs are not just for accomplishing the regulatory requirement, it aims to be part of the overall development and bring sustainable social reform. CG has livelihood as well as heritage and spiritual development programs which also should remain under CSR practices for the economic development of the country. The companies have disclosed relatively more philanthropic and ethical information and the least economic information. In this study, the economic domain of CSR is dominant. The economic domain of CSR includes the production of goods and services to earn profits. This is followed by a legal, philanthropic and ethical domain. This study helps the policymaker, business organizations, researchers, and learners to improve knowledge and ideas about CSR.